The Gondwanan relict oribatid genus Crotonia (Acari: Oribatida: Crotoniidae) from rainforests in Queensland and Northern New South Wales: new species show a mixed pattern of short-range and long-range endemism - Colloff, Matthew J. (Zootaxa, 2010)
Twelve new species of Crotonia are described from rainforests in Queensland and Northern New South Wales, Australia. Crotonia sterigma sp. nov. belongs to a new species group, Borbora, to which C. borbora Luxton, 1987, redescribed here, and for which a lectotype is designated, is re-assigned from the Capistrata group. Six species belong to the Capistrata group (C. brisbanensis sp. nov., C. maculata sp. nov., C. monteithi sp. nov., C. daviesae sp. nov., C. weiri sp. nov., and C. yeatesi sp. nov.). Previously-known Australian members of the Capistrata group, C. ardala Luxton, 1987 and C. capistrata Luxton, 1987, are redescribed and lectotypes are designated. Four species, C. cameroni sp. nov., C. queenslandiae sp. nov., C. eungella sp. nov. and C. seemani sp. nov., belong to the Cophinaria species-group and one, C. raveni sp. nov. is morphologically so different from other Crotonia spp. that it is also assigned to a new species-group. This brings the number of species of Crotonia recorded from Australia to 27, almost half of the global fauna. Mostspecies show localised distribution in rainforest remnants, characteristic of short-range endemics with apparently low dispersal capabilities, are subject to constraints of body water balance and thus confined to wet habitats. They can be divided into those associated with a northern region (ca. 16–18°S) centred around the Wet Tropics from Cape Tribulation to the Walter Hill Range (C. ardala, C. borbora, C. capistrata, C. monteithi), a central region (ca. 20–18°S) from Mount Dryander to Byfield (C. cameroni, C. eungella, C. seemani) and a southern region (ca. 26-28°S) from the Conondale Range to Whian Whian (C. brisbanensis, C. daviesae, C. queenslandiae, C. raveni, C. weiri, and C. yeatesi). Other species are long-range endemics. Crotonia maculata sp. nov. is found throughout all three regions and C. sterigma sp. nov. is found in both the central and southern regions. Several species show a series of characters that are considered to function in aiding the accumulation and retention of mineral soil and organic debris adhering to the cerotegument. These characters include the elongation of the caudal apophyses, expansion or elongation of the notogastral shield, retention of the elongated, flagelliform nymphal form of the notogastral setae and retention of nymphal exuviae in the caudal region. The layer of detritus covering the cerotegument was dissected off the cuticle of adult female and tritonymphal C. raveni sp. nov. and was found to constitute more than the mean wet weight of the mites. The acquisition by the mites of the detrital layer after each moult is considered to function as a general anti-predator system and in the reduction of body water loss.